Clinical value at baseline and follow-up of myeloperoxidase-antibodies in ANCA-associated vasculitis - Bossan, Gabriel; Roufosse, Florence; Vandergheynst, Frederic; Smet, Julie; Cogan, Elie; Vokaer, Benoit (Frontiers in Immunology, 2025)
BackgroundANCA-associated vasculitides (AAV) are potentially organ- or life-threatening disorders that can cause irreversible damage if treatment is not started in time. The course of the disease may vary once remission has been achieved, with some patients experiencing relapses while others remain in sustained remission. The predictive value of PR3-ANCA for clinical deterioration is well established. However, limited data regarding MPO-ANCA, which has primarily been studied in microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA), is less clear. This study aims to further clarify the role of MPO-ANCA in predicting relapse.MethodsWe conducted a retrospective review of the medical records of patients for whom positive MPO-ANCA serology was reported by our university laboratory between 2014 and 2024. We included patients who fulfilled the classification criteria for AAV and experienced remission. Remission was defined as a BVAS score of 0 and a prednisone-equivalent dose of less than 7.5 mg/day. We analyzed the impact of MPO-ANCA status (at diagnosis and over time) on the occurrence of relapse separately in patients with EGPA and patients with GPA/MPA. Relapse was defined as a BVAS score of 1 or higher.ResultsA total of 73 patients were included in the study, comprising 22 with EGPA and 51 with GPA/MPA. During follow-up (median 7 and 10yr, respectively), 10 EGPA and 19 GPA/MPA patients experienced a relapse. Baseline MPO-ANCA levels and eosinophil counts at diagnosis were not associated with the risk of relapse. However, an increase in MPO-ANCA levels during follow-up was significantly associated with clinical deterioration in both disease subgroups (positive predictive value 83% in EGPA, 79% in GPA/MPA; p = 0.0001). Median interval between an increase in MPO-ANCA levels and relapse was 3.6 ± 2.1 months and 4.6 ± 3.4 months, respectively. The initial pattern of organ involvement was a good predictor of the nature of disease manifestations at relapse. No relapses were observed in patients whose MPO-ANCA disappeared and remained negative (negative predictive value = 100%).ConclusionRegardless of AAV subtype, an increase in MPO-ANCA levels was associated with clinical deterioration. This study suggests that monitoring MPO-ANCA levels in AAV patients in remission could help clinicians to tailor therapy more effectively.